2011
DOI: 10.1002/dc.21743
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage improves diagnostic accuracy in patients with diffuse lung disease

Abstract: Bronchoalveolar lavage (BAL) is an established diagnostic tool in diffuse parenchyma lung disease. The objective of the present study was designed to investigate whether immunophenotyping affects BAL results and improves diagnostic accuracy. BAL from 61 patients was included in the study. The patients were also submitted to transbronchial biopsy, with a final diagnosis of granulomatous disease [tuberculosis (TB), n = 20; sarcoidosis (SARC), n = 3; and hypersensitivity pneumonitis (HP), n = 4]; idiopathic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…[78910] In this study, we found that the positive rate of pathogen detection in low respiratory tract was 61.6%, which was similar to the literature reported. [1112] The mixed infection was 3.1%, which was lower than the results reported before.…”
Section: Discussionsupporting
confidence: 88%
“…[78910] In this study, we found that the positive rate of pathogen detection in low respiratory tract was 61.6%, which was similar to the literature reported. [1112] The mixed infection was 3.1%, which was lower than the results reported before.…”
Section: Discussionsupporting
confidence: 88%
“…32,33 Some reports suggest an informative role of lymphocyte subset analysis (eg, CD4 to CD8 ratio) in sarcoidosis, but this test has no clear utility in fibrotic ILD. 30,34,35 There are no adequately designed studies evaluating whether BAL adds incremental diagnostic information beyond a thorough evaluation for alternative diagnoses in patients with fibrotic ILD.…”
Section: Bronchoalveolar Lavagementioning
confidence: 99%
“…However, collecting adequate amount of sputum from patients is not always possible, especially in children younger than 10 years old or in adults who cannot produce enough sputum. In situations like these, procedures to stimulate cough with an aerosol solution and/or bronchoalveolar or gastric lavage can be used (Capelozzi et al, 2011;Mohan et al, 1995;Somu et al,1995).…”
Section: Specimen Collectionmentioning
confidence: 99%